Clinical Trials for COVID‐19: Can we Better Use the Short Window of Opportunity?. Issue 4 (12th June 2020) - Eichler, Hans‐Georg; Cavaleri, Marco; Enzmann, Harald; Scotti, Francesca; Sepodes, Bruno; Sweeney, Fergus; Vamvakas, Spiros; Rasi, Guido
Abstract : The scientific community has risen to the coronavirus disease 2019 (COVID‐19) challenge, coming up with an impressive list of candidate drugs and vaccines targeting an array of pharmacological and immunological mechanisms. Yet, generating clinical evidence of efficacy and safety of these candidate treatments may be frustrated by the absence of comprehensive trial coordination mechanisms. Many small stand‐alone trials and observational studies of single‐agent interventions are currently running or in planning; many of these will likely not deliver robust results that could support regulatory and patient‐level treatment decisions. In this paper, we discuss actions that all stakeholders in the clinical trial ecosystem need to take to ensure that the window of opportunity during this pandemic will not shut, both for patients in need of treatment and for researchers to conduct decision‐relevant clinical trials.